Analysis of the Implementation of SAK EMKM In the Preparation of Financial Statements for MSMES: A Case Study of Kafe Maurani Simalungun Regency - Wico J Tarigan; Liharman Saragih; Mahaitin H Sinaga; Immanuelta Sitepu (Program Studi Akuntansi Universitas Simalungun, 2025)
This study aims to examine the implementation of financial statement preparation for the Micro, Small, and Medium Enterprise (MSME) Kafe Maurani based on SAK EMKM and to describe the challenges encountered in its implementation. This study is a descriptive qualitative research employing a case study approach. Data collection was carried out through interviews. The results of the study indicate that the financial statements prepared are not yet in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Furthermore, the information presented in the financial statements remains simple and is still based on cash inflows and outflows. The challenges faced by the owner in preparing the financial statements include a lack of understanding of financial reporting and limited time allocation